Efficacy of genetically engineered biological agents in the treatment of uveitis associated with rheumatic diseases in children - V V Neroyev; L A Katargina; E V Denisova; A V Starikova; N V Lyubimova (Научно-практическая ревматология, 2012)
The efficiency of incorporating genetically engineered biological agents (GEBAs) into a combination treatment regimen for rheumatic diseases (RD) (juvenile idiopathic arthritis, Behcet's disease) in relation to associated uveitis of varying severity was studied in 92 children aged 2 to 17 years. The follow-up lasted 1.5 to 49 months. Twenty-three patients took consecutively 2 to 5 GEBAs. When infliximab was used, remission of uveitis occurred in 21% of 38 children and the disease activity and/or recurrence rates reduced in an additional 21%. These were in 45 and 38.6% of 44 patients on adalimumab (ADA) and in 27.8 and 27.8% of 18 patients on abatacept, respectively. There was an association of the efficiency of therapy with the severity of uveitis at the start of treatment. The use of ADA induced a steady remission of panuveitis resistant to therapy with glucocorticoids and cyclosporine in both patients with Behcet's disease. One of 4 rituximab-treated patients achieved a steady remission. Tocilizumab therapy caused an exacerbation of uveitis in 1 patient. The postoperative period showed no inflammatory complications in most cases (37 operations, 26 eyes, 20 patients). No local adverse reactions were seen; systemic reactions occurred in 14% of the patients, this caused GEBAs to be discontinued in 7%. There is evidence for a need for further investigations into the efficacy of GEBAs in RD-associated uveitis in children in order to define success criteria, differentiated indications, and therapy regimens.